Managing Pregnancy and Delivery in a Patient with Von Willebrand Disease: A Case Report of Tailored Hemostatic Care - Rohina S. Aggarwal (Medical Science: Recent Advances and Applications Vol. 5, 2025)
Introduction: It is a lifelong bleeding disorder in which your blood doesn’t clot properly. People with the disease have low levels of von Willebrand factor, a protein that helps blood clot, or the protein doesn’t perform as it should due to a deficiency of Von Willebrand factor (VWF), either qualitative or quantitative. Both men and women are equally affected, and clinical presentation is more severe in females of reproductive age, and it is potentially life-threatening, particularly during labour and early puerperium. Aim of Study: To ascertain the importance of Von Willebrand Disease in Pregnancy and its multidisciplinary approach for management. Materials and Methods: The case of a 35-year-old Primigravida woman who had Von Willebrand disease diagnosed before she became pregnant, was described. Results: The institutional recommendation for addressing this condition includes getting and keeping ready Von Willebrand factor and factor VIII (FVIII) for administration throughout the caesarean delivery and in the postpartum period. This was ensured so as to increase Von Willebrand factor levels, and hence successful management of intrapartum and postpartum complications, along with preventing the need for blood and blood products transfusions and subsequent haemorrhagic shock. Though it was not administered throughout the stay of patient in the hospital. Conclusion: This case highlights the importance of following institutional protocol for ascertaining the presence of hemostatic agents during labour and early puerperium. Management of females with this illness throughout the antenatal, intrapartum and postpartum period, with the combined consultation of a multidisciplinary team comprising obstetricians, haematologists, and other medical specialists, is recommended. Since it is an inherited disorder, preconceptional counselling through to antenatal screening is recommended.